The effects of environmental factors on mortality and complex gill disease in Scottish farmed Atlantic salmon (Salmo salar L.) using a time series analysis - Ferreira, Ana Rita Isidoro (2022)
Dissertação de Mestrado Integrado em Medicina Veterinária